Regional Government Supervision on Coal Mine Voids in East Kalimantan Province - Muhammad Bagus Adi Wicaksono, I. Gusti Ayu Ketut Rachmi Handayani, Lego Karjoko (International Journal of Advanced Science and Technology, 2020)
Management of coal mine voids requires the role of regional government supervision in East Kalimantan to be performed effectively to realize the constitutional directions for using natural resources aimed at the community’s prosperity. This research used the normative juridical method. The results of the study concluded that the legislation implications of the government’s authority to supervise the transition of mining management have not been carrying out optimally to companies that have not conducted reclamation and law enforcement in the mining sector in criminal law have not been effective because since 2011 to 2019, the cases of several victims who died in the mine voids have not been imposed criminal penalties and administrative sanctions are still not effective because of not strict and slow follow-up by the Regional Government of East Kalimantan.